Biosynthesis of Silver Nanoparticles Using Abutilon indicum (Link): An Investigation of Anti-inflammatory and Antioxidant Potential against Carrageen Induced Paw Edema in Rats - Kumaran, Dr. N. Sri (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: In the present study, the synthesis of silver nanoparticle from ethanolic extraction of Abutilon indicum (Link) and its anti-inflammatory & antioxidant properties were studied. The bioactive compounds from Abutilon indicum were identified by gas chromatography and mass spectroscopy. The AgNPs synthesis was done using the ethanolic solution of A. indicum extract and silver nitrate. Materials and Methods: The AgNPs were characterized using ultraviolet (UV)-spectroscopic analysis, high-resolution transmission electron microscopy (HRTEM), and Fourier transform infrared spectroscopy (FTIR) analysis. The anti-inflammatory and antioxidants assays were followed by the standard methods. The mice bioassay study was conducted using doses of 50, 100, 150, and 200 mg/kg bw. Results: The presence of bioactive compounds from A. indicum is dodecanoic acid (8.846), octadecanoic acid (9.608), nonanoic acid (12.258), N-hexadecanoic acid (14.222), ethanol, 2-bromo (16.985), dibutyl phthalate (17.729), phytol (19.671), and diisooctyl phthalate (23.272). UV-visible spectral analysis shows a maximum absorption peak at 421.00 nm. The FTIR spectra of AgNPs exhibited prominent peaks represents such as alcohols, phenols, alkynes, aromatics, aldehydes, alkenes, aromatics, aliphatic amines, 1° and 2° amines, and alkyl halides. The HRTEM analysis of the synthesized AgNPs clearly showed the clustered and irregular shapes, mostly aggregated and having the size of 20 nm. The maximum inhibition of edema 39.49% was found in ethanolic extraction of A. indicum (200 mg/kg bw) and AgNPs of A. indicum (100 mg/kg bw) showed 55.98% at the end of 3 h. A significant increase in the activities of superoxide dismutase, catalase, glutathione peroxidase, vitamin-C and vitamin-E was observed in tissue of inflammation in rats on treatment with 100 mg/kg body weight of A. indicum extract and compared with standard and control groups. Conclusion: This study indicates the AgNPs synthesized A. indicum possesses anti-inflammatory and antioxidant potential which may be used for therapeutic purposes mainly in the prevention of oxidative damage that occurs during inflammation.